Interactive Digital Module for Elementary School Science and Social Studies Learning Using the Multimedia Development Life Cycle Method - Putra, Kurnia Ramadhan; Angelica, Evlyn; Adinda, Najwa; Rahmainingtias, Berka Ridha; Putri, Azzahra Candra; Utami, Azzila Deswita; Purwanti, Tri Rahayu; Putri, Windi Laudi; Wahidyah, Nazillah; Abigael, Hugo; Risyanti, Rifa Aulia (Universitas Teknokrat Indonesia, 2025)
This Community Service Program (PKM) addresses challenges in implementing interactive learning technology at SDN 150 Gatot Subroto, focusing on grades 4 and 5. It develops multimedia-based modules and provides teacher training using the Multimedia Development Life Cycle (MDLC) method, comprising five stages: initialization, blueprint design, asset preparation, product development, and testing. The modules include animations, navigation buttons, background music, and interactive quizzes to enhance student motivation and understanding. A SWOT analysis highlights strengths such as PowerPoint’s accessibility and the growing awareness of technology-based learning. However, infrastructure limitations and teacher resistance to technology pose challenges.Testing with 54 students showed over 50% could correctly answer quizzes, indicating the media effectively improves comprehension. The program concludes that interactive multimedia-based learning enhances student motivation and engagement. Recommendations include providing guide modules, regular teacher training, and teacher learning groups to support sustainable implementation. This program offers a lasting solution to improving elementary education through interactive multimedia.